The evolution of the Line of Variations at close encounters: an analytic approach - Valsecchi, G. B.; Del Vigna, A.; Ceccaroni, Marta (Springer, 2019)
We study the post-encounter evolution of fictitious small bodies belonging to the so-called Line of Variations (LoV) in the framework of the analytic theory of close encounters. We show the consequences of the encounter on the local minimum of the distance between the orbit of the planet and that of the small body and get a global picture of the way in which the planetocentric velocity vector is affected by the encounter. The analytical results are compared with those of numerical integrations of the restricted three-body problem
Keywords: Asteroid; Comet; Perturbation; Close encounter